2008
DOI: 10.1002/lsm.20602
|View full text |Cite
|
Sign up to set email alerts
|

Ablative targeting of fatty‐tissue using a high‐powered diode laser

Abstract: Background and Objective: Concerning current clinical practice, laser-assisted lipoplasty is still secondary to other procedures. In order to evaluate effects of thermal interaction with fatty-tissue, a near infrared diode laser was examined under reproducible conditions. Methods: Based on optical spectroscopy of fatty-tissue, a high-powered diode laser (l ¼ 940 nm) was used to irradiate n ¼ 59 fat samples of fresh corpses in non-contact mode. Thermal effects were histologically evaluated by computer based met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Removal of fat from adipocytes with a 635 nm laser has been claimed, but the evidence including histological studies are lacking [1,2]. When used invasively, in direct contact with the fatty tissue, various lasers such as carbon dioxide and Nd:YAG lasers have been shown to reduce subcutaneous fat [3][4][5]. Non-invasively achieved fat loss has been developed and/or claimed to occur using focused ultrasound [6,7], radiofrequency devices [8], and selective cryolysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Removal of fat from adipocytes with a 635 nm laser has been claimed, but the evidence including histological studies are lacking [1,2]. When used invasively, in direct contact with the fatty tissue, various lasers such as carbon dioxide and Nd:YAG lasers have been shown to reduce subcutaneous fat [3][4][5]. Non-invasively achieved fat loss has been developed and/or claimed to occur using focused ultrasound [6,7], radiofrequency devices [8], and selective cryolysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser irradiation of fat at these wavelengths may be an important breakthrough in the treatment of ''cellulite.'' O'Dey et al 33 showed fatty tissue ablation using a high-powered diode laser (l = 940 nm) using fat cells harvested from the anteromedial thigh in vitro. Their study showed that l = 940 nm achieves an increased absorption of both fatty tissue and water while maintaining a penetration depth of several millimeters.…”
Section: Ultrasoundmentioning
confidence: 99%
“…The authors primarily use a dual wavelength system that independently targets lipid and water-based tissues (SlimLipo™, Palomar Medical Technologies, Inc., Burlington, MA), which is cleared by the FDA for the indication of laser-assisted lipolysis. The wavelengths 924 and 975 nm were chosen based on a clear peak in the adipose tissue absorption spectrum at 924 nm and a peak in the water absorption spectrum at 975 nm, respectively [26,30]. In principle, absorption by the lipids of laser light at this 924 nm wavelength is of the appropriate strength to provide efficient penetration into the adipose tissue yet sufficient heating for the release of intracellular lipids while coagulating rather than tearing the nearby fibrous network needed for tissue tightening.…”
Section: Wavelength and Pulse Durationmentioning
confidence: 99%